Altered connectivity of the right anterior insula drives the pain connectome changes in chronic knee osteoarthritis - Cottam, William J.; Iwabuchi, Sarina J.; Drabek, Marianne M.; Reckziegel, Diane; Auer, Dorothee P. (Lippincott, Williams & Wilkins, 2018)
Resting-state functional connectivity (FC) has proven a powerful approach to understand the neural underpinnings of chronic pain, reporting altered connectivity in three main networks: the default mode (DMN), central executive (CEN), and the salience network (SN). The interrelation and possible mechanisms of these changes are less well understood in chronic pain. Based on emerging evidence of its role to drive switches between network states, the right anterior insula (rAI, an SN hub) may play a dominant role in network connectivity changes underpinning chronic pain. To test this hypothesis, we used seed-based resting-state FC analysis including dynamic and effective connectivity metrics in 25 people with chronic osteoarthritis (OA) pain and 19 matched healthy volunteers. Compared to controls, participants with painful knee OA presented with increased anticorrelation between the right anterior insula (SN) and DMN regions. Also, the left dorsal prefrontal cortex (CEN hub) showed more negative FC with the right temporal gyrus. Granger causality analysis revealed increased negative influence of the right anterior insula on the posterior cingulate (DMN) in OA patients in line with the observed enhanced anticorrelation. Moreover, dynamic FC was lower in the DMN of patients and thus more similar to temporal dynamics of the SN. Together, these findings evidence a widespread network disruption in patients with persistent osteoarthritis pain, and point toward a driving role of the rAI.